Penerapan Teori Interaksi Simbolik dan Perubahan Sosial di Era Digital - Hasbullah, Abdur Rouf; Ahid, Nur; Sutrisno (At-Tahdzib: Jurnal Studi Islam dan Muamalah, 2022)
Background. The digital era is the historical period characterized by the existence of digital technology, including communication and social interaction. The unrealized discoveries in the field of technology will also affect social change greatly, and will also have a very serious impact on education indirectly.Aim. This paper will elaborate how the theory of symbolic interaction and the theory of social change as a collaborative approach in carrying-out social research and solutions in dealing with the current digital era. the qualitative approach is used in this research with a critical-analytic method to a social case.Methods. Library research was conducted to analyze the theory of this social change as the data took from many kinds of literature that contained this theory.Results. Explained in this paper the theory of symbolic interaction initiated by George Herbert Mead and later completed by Herbert Blumer. This symbolic interaction theory has three main key concepts: mind, self, society where the symbols of attitudes, behavior, ways of speaking are seen in the interactions that take place. Meanwhile, the theory of social change initiated by Auguste Comte and Herbert Spencer is a theory about changes in the structure of society that can affect the patterns of social interaction and something that can build human character towards a better process or vice versa.